5S Methodology to Increase Productivity in a Hardware Company's Warehouse in Lima - Campos Castro, Crhistiam (2024)
This study focuses on a population and sample consisting exclusively of orders that include a total of 5 items. The main purpose of this study is as follows: "To determine whether the implementation of the 5S methodology increases productivity in the warehouse area of Grupo Codise S.A.C." This study followed an applied methodology with a quantitative approach, at an explanatory level, and had an Experimental - Pre-experimental design. To collect data, the observation technique was used to conduct a detailed analysis of activities in the warehouse. Various instruments were employed, such as the Process Affinity Diagram (DAP), the Ishikawa Diagram, and checklists. Instrument validation and the use of a stopwatch were carried out, considering instrument reliability. The collected quantitative data was managed in Microsoft Excel and analyzed using the SPSS software, where both the general and specific hypotheses were evaluated. This analysis revealed that the implementation of the 5S methodology resulted in a 12.62% increase in productivity. Furthermore, improvements in efficiency of 4% and effectiveness of 8.4% were observed. In summary, the findings highlight the positive impact of the 5S methodology, enhancing both efficiency and effectiveness of operations.